2011
DOI: 10.1007/s00442-011-2026-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing donor ecosystem productivity decreases terrestrial consumer reliance on a stream resource subsidy

Abstract: Because nutrient enrichment can increase ecosystem productivity, it may enhance resource flows to adjacent ecosystems as organisms cross ecosystem boundaries and subsidize predators in recipient ecosystems. Here, we quantified the biomass and abundance of aquatic emergence and terrestrial spiders in a reference and treatment stream that had been continuously enriched with nitrogen and phosphorus for 5 years. Because we previously showed that enrichment increased secondary production of stream consumers, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 43 publications
3
39
1
Order By: Relevance
“…We found that nutrient addition led to an increase in MeHg flux from aquatic ecosystems, primarily through enhancing the biomass of emerging insects whose tissues were contaminated with MeHg. The bottom-up effect of nutrients on the flux of resource subsidies (i.e., emerging insects) to terrestrial ecosystems has previously been demonstrated across productivity gradients in field studies [29] and in systems that have been experimentally manipulated [10][11][12]30]. The present study suggests that increased nutrient inputs into aquatic ecosystems increases the risk that terrestrial consumers will be exposed to greater fluxes of aquatically-derived MeHg.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We found that nutrient addition led to an increase in MeHg flux from aquatic ecosystems, primarily through enhancing the biomass of emerging insects whose tissues were contaminated with MeHg. The bottom-up effect of nutrients on the flux of resource subsidies (i.e., emerging insects) to terrestrial ecosystems has previously been demonstrated across productivity gradients in field studies [29] and in systems that have been experimentally manipulated [10][11][12]30]. The present study suggests that increased nutrient inputs into aquatic ecosystems increases the risk that terrestrial consumers will be exposed to greater fluxes of aquatically-derived MeHg.…”
Section: Discussionsupporting
confidence: 60%
“…The bottom-up effects of nutrients potentially influence the flux of MeHg from aquatic systems by regulating productivity and emergent insect biomass [10][11][12]. Nutrients may also alter the flux of MeHg by affecting the concentrations of MeHg of insects as has been shown for other consumers [13][14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…Changes to the aquatic environment that alter the habitat and food resources available for aquatic larvae also alter the abundance and identity of adult aquatic insects emerging from a river (Compson et al 2013), with flow-on effects to terrestrial consumers (Epanchin et al 2010). However, relatively little is known about how anthropogenic factors may affect the supply and consumption of adult aquatic insects by terrestrial consumers (but see Davis et al 2011;Greig et al 2012;Jonsson et al 2013;Paetzold et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Such taxa are often molluscus and worms (Harding and Winterbourn 1995), which do not have winged adult stages. However, eutrophic conditions or nutrient additions can also increase emergence rates of Diptera (Davis et al 2011;Greig et al 2012;Welch et al 1988), which may increase the number of terrestrial consumers that a waterway can support (Racey et al 1998). Anthropogenic alterations to river flow regimes through water abstraction, river channelisation, dams or changes to the climate can alter the intensity, frequency and seasonal predictability of high and low river flows (Poff et al 1997), which may lead to changes in aquatic invertebrate communities (Meyer et al 1999).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation